2018
DOI: 10.25130/tjps.23.2018.007
|View full text |Cite
|
Sign up to set email alerts
|

Study the effect of Metronidazole Drug (MTZ) and Rhuscoriaria (Sumac) on Testicular Tissues and sperms of Male White Mice

Abstract: In this study, thirty adult Swiss male mice weighing with an average weight of twenty seven gram were used. The animals were housed in animal house of the college of Veterinary Medicine/ Tikrit University under normal conditions. The whole animals were divided into three groups each of ten mice, and subdivided into two periods (fourteen and twenty eight days), first group considered as control which were administered with distilled water only. The second group was treated with the metronidazole (MTZ) at a dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…These authors attributed this effect to the action of metronidazole on the ovarian follicles of the treated females, dismissing a post-fertilization effect since the administration of the drug occurred before mating. Furthermore, studies showed cytotoxicity of this drug in studies about germ cells (El-Nahas and El-Ashmawy, 2004;Rasheed et al 2018), also indicating the possibility of a cytotoxic effect in some released oocytes.…”
Section: Discussionmentioning
confidence: 91%
“…These authors attributed this effect to the action of metronidazole on the ovarian follicles of the treated females, dismissing a post-fertilization effect since the administration of the drug occurred before mating. Furthermore, studies showed cytotoxicity of this drug in studies about germ cells (El-Nahas and El-Ashmawy, 2004;Rasheed et al 2018), also indicating the possibility of a cytotoxic effect in some released oocytes.…”
Section: Discussionmentioning
confidence: 91%